Clearing for Deep Tissue Imaging. Issue 1 (13th July 2018) - Muntifering, Michael; Castranova, Daniel; Gibson, Gregory A.; Meyer, Evan; Kofron, Matthew; Watson, Alan M.
Abstract: Biologic tissues are generally opaque due to optical properties that result in scattering and absorption of light. Preparation of tissues for optical microscopy often involves sectioning to a thickness of 50‐100 µm, the practical limits of light penetration and recovery. A researcher who wishes to image a whole tissue must acquire potentially hundreds of individual sections before rendering them into a three‐dimensional volume. Clearing removes strongly light‐scattering and light‐absorbing components of a tissue and equalizes the refractive index of the imaging medium to that of the tissue. After clearing, the maximum depth of imaging is often defined by the microscope optics rather than the tissue. Such visibility enables the interrogation of whole tissues and even animals without the need to section. Researchers can study a biological process in the context of its three‐dimensional environment, identify rare events in large volumes of tissues, and trace cells and cell‐cell interactions over large distances. This article describes four popular clearing protocols that are relevant to a wide variety of scenarios across biologic disciplines: CUBIC, CLARITY, 3DISCO, and SeeDB. © 2018 by John Wiley & Sons, Inc.